PEMBUATAN MEMBRAN KERAMIK BERPORI BERBASIS CLAY DENGAN VARIASI ZEOLIT DAN PENAMBAHAN ARANG AKTIF TEMPURUNG KELAPA SERTA POLIVINYL ALCOHOL - Mochamad Kurniwan; Agus Setyo Budi; Anggoro Budi Susilo (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2014)
Membrane separator is a selective barrier that can separate the two phases of the various mixtures (Fauzan, 2009). In this research be made of porous ceramic membranes based on clay with variations zeolite and additives of coconut shell charcoal as well as PVA are made in several different compositions. Zeolite and clay are the main materials of ceramic membrane, whereas coconut shell charcoal and PVA are the additives materials. Tests conducted using water absorption test, density test, and porosity test of the ceramic membrane. The calculation of density and porosity based on ASTM C 20-92 standard with toluena, whereas verification the functionality of ceramic membrane can be adsorb Fe content in groundwater be used AAS, as well as testing SEM to see microstructure membrane formed. The research obtained to the values of water absorption test are 19,802-47,689 %, the values of density test are 0,610-0,953 g/cm3, and the values of porosity test are 21,701-33,446 %. From tested and measured of the sample, can be identified that additives decreased the roughness and density of the sample, increased the absorption and porosity of the sample. Keywords: water absorption, density, porosity, AAS, SEM.